Teaching Strategies in Virtual Public Speaking During the COVID-19 Pandemic - Rupidara, Nining N. (Huele: Journal of Applied Linguistics, Literature and Culture, 2023)
The COVID-19 pandemic precipitated an unprecedented shift to online learning, particularly affecting public speaking courses that traditionally rely on face-to-face interaction. This qualitative study investigates the teaching strategies employed by lecturers in online public speaking courses at Pattimura University's English Education Study Program. Using Fortune's (2000) observation checklist, the research examined twelve teaching sessions conducted by two lecturers teaching forty students over one semester. Data collection involved classroom observations, lecturer interviews, and document analysis. The findings revealed five primary teaching strategies successfully adapted for online delivery: brainstorming, group discussions, writing tasks, picture descriptions, and presentations/talks. Analysis of implementation patterns showed varying degrees of effectiveness across different strategies, with technical challenges significantly impacting delivery. The study documented specific patterns in strategy application across three observation periods, with brainstorming predominantly used in initial sessions, group discussions and writing tasks in intermediate stages, and picture descriptions and presentations in later sessions. Technical difficulties, particularly internet connectivity and platform stability, emerged as persistent challenges, affecting both strategy implementation and student participation. The research also highlighted the evolution of assessment methods to accommodate online delivery constraints while maintaining pedagogical effectiveness. These findings contribute to the growing body of knowledge about online teaching methodologies and provide practical insights for educators adapting public speaking instruction to virtual environments. The study concludes with recommendations for improving online public speaking instruction through enhanced technical infrastructure, professional development, and balanced activity design.